1959
DOI: 10.1111/j.1476-5381.1959.tb00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiphlogistic Activity of Iproniazid

Abstract: Iproniazid was found to inhibit formalin-induced oedema of the foot, dextran-induced oedema and cotton-pellet-induced granulomatous tissue in the rat. The presence of the adrenals was essential for the antiphlogistic activity. The antiphlogistic action was not accompanied by any antipyretic effect. Inhibition of formalin-induced oedema was also observed with phenylbutazone and with salicylamide.Little is known about the therapeutic efficacy and mechanism of action of iproniazid in rheumatoid arthritis. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1960
1960
1969
1969

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…Methocarbamol, amidopyrine and phenylbutazone, however, were highly active, whereas the four aryloxypropionates tested and sodium acetylsalicylate were moderately active. The activity of phenylbutazone confirmed the observations of Setnikar, Salvaterra & Temelcou (1959). In the cortisone-maintained adrenalectomized mice both sodium salicylate and B.C.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Methocarbamol, amidopyrine and phenylbutazone, however, were highly active, whereas the four aryloxypropionates tested and sodium acetylsalicylate were moderately active. The activity of phenylbutazone confirmed the observations of Setnikar, Salvaterra & Temelcou (1959). In the cortisone-maintained adrenalectomized mice both sodium salicylate and B.C.…”
Section: Resultssupporting
confidence: 73%
“…Selye (1949) has shown that in the adrenalectomized rat both cortisone and adrenocorticotrophic hormone are effective in antagonizing the reaction to formaldehyde. It has been reported by Setnikar, Salvaterra & Temelcou (1959) that the swelling of the rat foot caused by an injection of formaldehyde can be partially prevented by iproniazid, phenylbutazone and salicylamide. Recently, Buch (1959) has shown that various phenylpropylcarbamates are effective in reducing the reaction to formaldehyde.…”
mentioning
confidence: 99%
“…Other areas containing histamine but less 5-HT exhibit this response weakly [910J; g) subcutaneous injection into the rat paw of dextran or turpentine oil produces a significant reduction (from 0·75 to 0-22-0-28 /kg/g) of the 5-HT content not only in the injected paw but also in the opposite untreated paw [1183bJ_ Sustainers of the theory that multiple agents are involved in the pathogenesis of the anaphylactoid reaction object that substances which produce this reaction release 5-HT as well as histamine from skin tissues [908,847,539]; that higher doses of BOL or LSD are required to block anaphylactoid reaction than to block oedema produced by 5-HT [847b]; that while Dibenamine® regularly inhibits the oedema produced by 5-HT, and pyrilamine that produced by histamine, both drugs are necessary to block the oedema-producing action of ovomucoid [1010]; that pretreatment with the MAO-inhibitor iproniazid does not affect dextran oedema, contrary to expectation [36,846,1092]; that oedema produced by 5-HT, even after the highest doses which can be tolerated, is never as marked as that obtained with substances capable of producing an anaphylactoid inflammation; that oedema produced by histamine, dextran or formaldehyde is inhibited to a great extent by pretreatment with glucagon (1 mg/kg), whereas 5-HT oedema is not significantly changed [713 b] ; that 48/80 even given repeatedly does not produce any change in the urinary excretion of 5-HIAA and rats given compound 48/80 in increasing doses for 8 days excrete as much 5-HIAA after injection of reserpine as the untreated controls do [618b];…”
Section: Anaphylactoid Reactionmentioning
confidence: 99%
“…Tests involving the inhibition of dextran-induced oedema in rats have been described for the quantitative evaluation of antihistamines (Stucki & Thompson, 1958;KMt6 & Gozsy, 1960c and anti-inflammatory compounds (Setnikar, Salvaterra & Temelcou, 1959). The present results show that, when a strain of rat which contains some non-reactors is used, then by chance the resistant animals may be unequally distributed between the test and control groups.…”
Section: Harris and G B Westmentioning
confidence: 59%
“…Tests involving the inhibition of dextran-induced oedema in rats have been described for the quantitative evaluation of antihistamines (Stucki & Thompson, 1958;KMt6 & Gozsy, 1960c and anti-inflammatory compounds (Setnikar, Salvaterra & Temelcou, 1959 (Kabat & Berg, 1953)-then it is likely that this antibody to dextran is lacking in non-reactor rats. The difference between the reactions to dextran in rats of the two types used in the present study is in any case genetically controlled.…”
Section: Harris and G B Westmentioning
confidence: 99%